Analysis improves selection of rheological model for slurries - MOFTAH, K (The Oil & gas journal, 1993)
The use of a statistical index of determination can help select a fluid model to describe the rheology of oil well cement slurries. Cement slurries for oil wells are normally treated as Bingham plastic or power law fluids. The Bingham plastic model is a linear regression of the shear stress as the dependant variable and the shear rate as the independent variable. The power law model is the linear regression of the logarithms of the shear stress and the shear rate on the same axes. One drawback inherent in the Bingham plastic model is that some regression analyses can produce a negative yield stress, and a negative yield stress is meaningless. The reason that some slurries produce negative yield stresses is examined. A computer program written in Quick Basic to calculate rheological parameters and an index of determination for the Bingham plastic and power law models are described.